Composite particles and toners
Patent Information
- Application Number
- JP2020051534
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-23
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-03-23
AI Technical Summary
【0011】 上述する構成を備える本発明の複合粒子は、分散性が良好であり、凝集することが防止される。かかる本発明の複合粒子をトナー部材として用いた場合、半導体デバイスなどにも適用可能な高精細の金属配線を印刷可能である。もちろん、当該トナー部材を用いてトナー印刷により金属配線を印刷した場合には、上述するインクジェットなどが有していた環境問題やコーヒーリングの発生が防止されることは言うまでもない。
Smart Images

Figure 0007640063000002 
Figure 0007640063000003 
Figure 0007640063000004
Abstract
Description
[Technical field]
[0001] The present invention relates to composite particles and toners. [Background technology]
[0002] Currently, printing technologies such as inkjet printing and gravure printing are being widely researched as manufacturing technologies for flexible organic semiconductor devices, etc. These technologies are called printed electronics, and are expected to be useful because they make it possible to apply the required amount of material to the desired location, do not require vacuum processes as in conventional semiconductor manufacturing technologies, and enable large-area and high-speed printing.
[0003] However, printed electronics has the following problems. That is, currently, printed electronics is mainly produced by dissolving or dispersing materials such as metals, semiconductors, and insulating materials in an appropriate solvent to produce ink, which is then used in printing techniques such as inkjet printing and gravure printing. Here, volatile organic solvents such as halogen-based solvents and aromatic solvents are generally used as the solvent for the ink, but these volatile organic solvents are problematic not only in terms of the direct impact on workers but also in terms of global environmental conservation.
[0004] Meanwhile, a method for developing an electrostatic latent image using conductive particles such as metal powder has been proposed (Patent Document 1 below). The above-mentioned developing method is a technology related to a developing method using a developer in which conductive particles consisting essentially of only conductive materials and resin carrier particles are mixed. According to Patent Document 1, since the image pattern formed by the above-mentioned developing method is made of conductive particles consisting essentially of conductive materials, the image pattern can be subjected to post-treatment such as baking to impart conductivity as an electric circuit, and the image pattern can be used to form an electric circuit within a semiconductor integrated device, for example. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-257684 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the above-mentioned printed electronics, the inventors have focused on toner printing using conductive particles, taking into consideration the problems of printing techniques using ink such as inkjet printing. Printed electronics using toner printing does not require chemical modification or special solvents required for ink production, so that the environmental impact can be reduced. In addition, since inkjet printing is a dot printing method, when the ink transferred in a dot shape dries, the components may concentrate in a ring shape around the edge of the dot, which is called the coffee ring phenomenon. The coffee ring phenomenon causes printing unevenness, and therefore, when trying to pattern an electric circuit, it can be an obstacle to high resolution and can also be a factor in increasing electrical resistance. In contrast, with toner printing, there is no need to worry about the coffee ring phenomenon.
[0007] The technology disclosed in the above-mentioned Patent Document 1 uses conductive particles, and therefore allows for patterning of electric circuits, but the inventors have found that this technology is difficult to pattern high-definition electric circuits and difficult to achieve high integration of semiconductors. In other words, the current situation is that toner printing that is substantially compatible with printed electronics has not yet been realized.
[0008] In view of the above problems, the present invention has been made with a view to enabling toner printing that is substantially suitable for printed electronics. More specifically, the present invention aims to provide composite particles and toner that are environmentally friendly and enable printing of high-definition metal wiring that can be applied to semiconductor devices, etc. [Means for solving the problem]
[0009] The composite particles of the present invention are Consists of only conductive materials The toner particles for forming metal wiring include conductive particles and coated particles made of a material different from the conductive particles (excluding thermoplastic resin), the coated particles include a conductive material, and at least a portion of the surface of the conductive particles is coated with the coated particles.
[0010] The toner of the present invention is characterized by containing the composite particles of the present invention as toner particles. Effect of the Invention
[0011] The composite particles of the present invention having the above-mentioned configuration have good dispersibility and are prevented from agglomerating. When such composite particles of the present invention are used as a toner member, it is possible to print high-definition metal wiring that can be applied to semiconductor devices, etc. Of course, when the toner member is used to print metal wiring by toner printing, it goes without saying that the environmental problems and coffee ring that the inkjet printers described above have are prevented. [Brief description of the drawings]
[0012] [Figure 1] 1 shows an SEM photograph of a composite particle according to an example of the present invention, with an analytical image of nickel element analyzed by energy dispersive X-ray analysis (EDX analysis) performed using the composite particle superimposed thereon. [Diagram 2] 1 is a scanning microscope photograph of the composite particles of Example 1. [Diagram 3] 1 is a scanning microscope photograph of the composite particles of Example 3. [Figure 4] 1 is an electron microscope photograph of silver particles before stirring in Comparative Example 1. [Diagram 5] 1 is an electron microscope photograph of the silver particles of Comparative Example 1 after being stirred in a ball mill. [Figure 6] FIG. 13 is a schematic diagram of a developing device used in toner printing according to Example 5. [Figure 7] 13 is a photomask pattern used in toner printing in accordance with Example 5. [Figure 8]1 is an electron microscope photograph of a conventional two-component toner prepared by mixing carrier particles and silver particles in a ball mill. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present inventors have conducted extensive research to enable high-definition patterning by toner printing in printed electronics. As a result, they have found that the main cause of difficulty in high-definition patterning when toner printing is performed using general conductive particles is the aggregation of the conductive particles. In other words, conductive particles used in printed electronics are preferably those having an average particle size of, for example, nano-size to several tens of microns, but conductive particles with such an average particle size tend to aggregate together and form clumps. FIG. 4 is an electron microscope photograph of silver particles (manufacturer catalog value; average particle size of about 2 μm to 3, 5 μm) in Comparative Example 1 described later, and according to FIG. 4, it can be seen that the silver particles are in clumps of about several tens of microns. Even if these silver particles are stirred with a ball mill or the like, they do not become smaller in particle size, but tend to be crushed in clump form as shown in FIG. 5 to form clumps of large and flat silver particles. Note that FIG. 5 is an electron microscope photograph of silver particles in Comparative Example 1 described later after stirring with a ball mill. When toner printing is performed using silver particles that have become agglomerated in this way and have a large apparent particle size, high-resolution patterning is difficult and printing unevenness is likely to occur. In other words, it was presumed that the main reason why high-resolution patterning was difficult in toner printing using conventional conductive particles was that the silver particles became agglomerated and the apparent particle size was large.
[0014] In toner printing, a charged toner component is transferred to a target electrode that has been exposed to light and has a high voltage in a specific area, and development is performed. Here, a two-component development method is known in which a toner containing particles called carrier particles is used together with the toner component to carry and charge the toner component before development. When preparing a toner used in the two-component development method, the toner component and the carrier particles are generally mixed together and stirred. By such stirring, the toner component is carried by the carrier particles and charged, and is transferred to the target electrode in the developing device to form a transfer product.
[0015] However, when the toner component, which is a conductive particle, and the carrier particle are mixed by a ball mill or the like, it was found that the conductive particles (or clumps thereof) of several microns or less can be supported on the surface of the carrier particle, but the conductive particles aggregated to a larger size are difficult to be supported on the surface of the carrier particle. A specific example is shown in FIG. 8. FIG. 8 is an electron microscope photograph of a two-component toner prepared by measuring 2 parts by mass of carrier particles (1793A4451, manufactured by Powder Tech Co., Ltd.; average particle size 70 μm) and 0.2 parts by mass of silver particles (Silver Nanopowder, manufactured by Sigma-Aldrich; average particle size 150 nm) and stirring the measured carrier particles and silver particles in a ball mill at 600 rpm for 30 minutes. As can be seen from FIG. 8, although small-diameter silver particles (or clumps thereof) are supported on the surface of the carrier particle, a large amount of large-diameter clumped silver particles exceeding 10 μm are present around the carrier particle without being supported. When such a two-component toner is used, the unsupported aggregated silver particles are difficult to migrate to the target electrode, so the amount of silver particles transferred is small and the transfer efficiency tends to be poor. Also, when the unsupported large aggregated silver particles migrate to the target electrode, the resolution of the developed pattern is poor because of their large diameter. For the above reasons, it was presumed that it would be difficult to achieve high-definition patterning when toner printing is performed using a conventional two-component toner containing conductive particles and carrier particles.
[0016] The present invention makes it possible to solve the above-mentioned various problems by improving the dispersibility of the conductive particles used in toner printing and suppressing aggregation. Specifically, in the composite particles of the present invention, at least a part of the surface of the conductive particles is covered with covering particles made of a material different from that of the conductive particles. The composite particles of the present invention having such a configuration are suppressed from agglomerating into clumps. Therefore, when the composite particles are used as a toner component for toner printing, high-definition patterning is possible. In addition, since the composite particles of the present invention have good dispersibility even when small in diameter, when the composite particles are mixed and stirred with carrier particles in a ball mill or the like to prepare a toner, the proportion of the composite particles carried on the surface of the carrier particles is high. Therefore, when the toner is printed using the toner, high-definition and high-resolution patterning (development) is possible. According to the present invention, which enables high-definition patterning in this way, it is possible to promote high integration of semiconductor devices and the like.
[0017] In the present invention, the coated particles are made of a different material from the conductive particles, which means that the main components constituting the coated particles and the conductive particles are different. In this specification, the main component means a component contained in an amount of more than 50 mass% in 100 mass% of the particles, and the main component is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more in 100 mass% of the particles. The main components of the conductive particles and the coated particles will be described later. The composite particles of the present invention will be described in more detail below.
[0018] [Composite particles] (Conductive particles) The conductive particles in the present invention are particulate matter that includes a substance that exhibits electrical conductivity. The conductive substance here refers to a substance that has the property of easily flowing electricity, and examples thereof include silver, gold, copper, nickel, tin oxide such as indium tin oxide and tin-antimony oxide, and carbon materials such as graphite, carbon nanotubes, and graphene, and these components are preferably the main components of the conductive particles. Among them, silver, gold and copper are preferred as components of the conductive particles of the present invention because they have low electrical resistivity and high conductivity, and silver and gold are more preferred as components of the conductive particles of the present invention because they are more suitable as members for printing and forming fine electrical wiring that is directly bonded to a semiconductor. Note that gold particles and silver particles are particles that have high activity on the particle surface and are particularly prone to aggregation, but according to the present invention, even when conductive particles containing gold or silver are used, the aggregation of particles can be well suppressed, and high-definition electrical circuits, etc. can be patterned by utilizing the high conductivity of gold and silver.
[0019] The conductive particles are composed of a material exhibiting the above-mentioned conductivity, and preferably, in 100 mass% of the conductive particles, the material exhibiting conductivity is contained in an amount of more than 50 mass%, more preferably 80 mass% or more, and even more preferably 90 mass% or more.
[0020] The average particle size of the conductive particles is not particularly limited, but from the viewpoint of enabling highly precise patterning more sufficiently, it is preferably in the range of 10 nm to 10 μm, more preferably 100 nm to 8 μm, and even more preferably 500 nm to 5 μm. The average particle size of the conductive particles can be, for example, reference to the values in the manufacturer's catalog of commercially available particles used as the conductive particles.
[0021] The conductive particles in the present invention conveniently include individual particles that are not aggregated at all and small-diameter aggregates formed by a small amount of individual particles. The average particle size of the conductive particles described above refers to the average particle size of the conductive particles alone.
[0022] (Coated particles) The coated particles in the present invention are particles made of a material different from that of the conductive particles. The conductive particles are particles made of different materials, and the aggregation of the composite particles can be suppressed by coating at least a portion of the surface of the conductive particles, where coating refers to a state in which small particles are attached to the surface of the conductive particles. More specifically, coated particles are present on the surface of the composite particle of the present invention, as shown in Figure 1. Figure 1 shows an SEM photograph of a composite particle as an example of the present invention, overlaid with an analytical image of nickel element analyzed by energy dispersive X-ray analysis (EDX analysis) performed using the composite particle. The lumps seen throughout the figure are the composite particles, and the presence of nickel is indicated by numerous fine dots on the surface. The composite particles shown in Fig. 1 were prepared by placing commercially available silver particles with an average particle size of 2μm to 3.5μm and nickel particles with an average particle size of 100nm or less in a screw-top test tube together with zirconia balls (average particle size of about 0.9mm to 1.1mm) as stirring members, and rotating the screw-top test tube with a ball mill to stir the contents. SEM photographs of the composite particles prepared in this way were taken, and elemental analysis was performed by energy dispersive X-ray analysis (EDX analysis), confirming that nickel particles, which are coating particles, were attached to the surfaces of the silver particles, which are conductive particles.
[0023] In the present invention, the coated particles are preferably smaller in diameter than the conductive particles. The average particle size of the coated particles is not particularly limited to a numerical range, but is preferably 5 nm or more and 5 μm or less, more preferably 10 nm or more and 1 μm or less, and even more preferably 30 nm or more and 500 nm or less. When the average particle size of the coated particles is 5 nm or more, the coated particles are easy to prepare or obtain, and when the average particle size of the coated particles is 5 μm or less, the surfaces of the conductive particles are easily coated. The average particle size of the coated particles can be, for example, reference to the manufacturer's catalog value of commercially available particles used as the coated particles.
[0024] The material constituting the coated particles is not particularly limited as long as it is different from the material constituting the conductive particles. For example, from the viewpoint of improving the electrical conductivity of the composite particles, it is preferable that the coated particles contain a conductive material. For example, tin oxides such as indium tin oxide and tin-antimony oxide, carbon materials such as graphite, carbon nanotubes, and graphene, and nickel are suitable as components of the coated particles, and it is preferable that these components are the main components in the coated particles.
[0025] From another point of view, the coated particles preferably contain a magnetic material, and for example, nickel, a nickel-iron alloy exhibiting magnetism, ferrite, etc. are suitable as components of the coated particles. The composite particles in which the surface of a conductive particle is coated with a coated particle containing a magnetic material can behave like a magnetic material, and these components are preferably the main components of the coated particles. When the composite particle of such an embodiment is used as a toner member, the toner member (composite particle) can be smoothly transferred to the target electrode, and the transfer efficiency can be improved. In addition, in the conventional two-component toner, the conductive particles are charged by carrying the conductive particles on the surface of the carrier particles, but if the composite particle has a conductive particle coated with a magnetic material, the composite particle itself becomes magnetic, so charging by the carrier particles is not required. Therefore, the composite particle of the present invention in an embodiment containing a magnetic material can be used as a toner component of a carrier-less toner that does not have a carrier particle.
[0026] In the present invention, the components of the conductive particles and the components of the coated particles may be different materials, but a particularly preferred combination is one in which the conductive particles contain silver particles or gold particles and are coated with conductive coated particles such as nickel particles and ITO particles. The conductive coated particles can also be made conductive to improve the conductivity of the composite particles. The nickel particles or ITO particles effectively suppress the aggregation of the silver particles and gold particles.
[0027] The composite particles of the present invention, which are composed of the above-mentioned conductive particles and coated particles, may contain components other than the conductive particles and composite particles within the scope of the present invention, but it is preferable that the composite particles are composed essentially of only the conductive particles and composite particles. The conductive particles in the composite particles of the present invention may be single conductive particles or small-sized aggregates of single conductive particles. When the conductive particles in the composite particles are small-sized aggregates, the coated particles may adhere to at least the surfaces of the aggregated conductive particles, and the coated particles may be present between the single conductive particles.
[0028] The average particle size of the composite particles of the present invention is not particularly limited, but the average particle size is preferably in the range of 10 nm to 30 μm, more preferably 100 nm to 10 μm, and even more preferably 500 nm to 7 μm. Composite particles having an average particle size of 10 nm or more are easy to handle, and by using composite particles having an average particle size of 30 μm or less, printing unevenness can be suppressed in toner printing, and high-definition patterning can be easily achieved, which is preferable. The particle size of the composite particles can be measured by observation under an electron microscope. When determining the average particle size, the longest diameter of a number of composite particles (e.g., 50 particles) randomly selected during observation under an electron microscope is measured, and the average particle size is calculated by arithmetically averaging these measured values.
[0029] The composite particles of the present invention described above have good dispersibility and suppressed aggregation, so they have excellent fluidity and are easy to handle. The fluidity of the composite particles can be confirmed, for example, by measuring the angle of repose of a control sample containing only the conductive particles used in the composite particles, and the composite particles themselves. In general, the angle of repose of the composite particles is smaller than the angle of repose of the conductive particles themselves used in the composite particles, and it can be confirmed that the composite particles have high fluidity.
[0030] The use of the composite particles of the present invention described above is not particularly limited, but it is a preferred embodiment that the composite particles of the present invention are used as toner particles for forming metal wiring. That is, the composite particles of the present invention are conductive because they use conductive particles, and are provided with coated particles to suppress aggregation, so they are useful as toner particles contained in a toner used to print and form metal wiring in a fine pattern.
[0031] [toner] The present invention encompasses a toner containing the composite particles of the present invention described above as toner particles. The toner of the present invention contains the composite particles of the present invention in which aggregation is suppressed as toner particles. Therefore, when electrostatic transfer is performed in a transfer device (developing device) using the toner of the present invention, high-definition patterning is possible. This solves the problems in printing techniques using inks such as inkjet printing in printed electronics, and enables high-definition patterning while being environmentally friendly. Moreover, although the composite particles, which are toner particles, are coated on the surface with coating particles, metal wiring formed using them can exhibit sufficiently low electrical resistance and has good electrical performance. Furthermore, the transferred material formed by transferring toner particles to the target electrode can be covered with an appropriate cover film in a later process and melted or sintered by ultrasonic sintering or the like to form metal wiring. EXAMPLES
[0032] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these. The details of the materials of the composite particles shown in Table 1 are as follows. (Conductive particles) Silver particles: Silver powder (327085-10G), average particle size 2μm~3.5μm, manufactured by Sigma-Aldrich Gold particles: Gold powder (326585-500MG), average particle size 10 μm or less, manufactured by Sigma-Aldrich (Coated particles) Nickel particles: Nickel nanopowder (577995-5G), average particle size 100 nm or less, manufactured by Sigma-Aldrich ITO particles: Indium tin oxide nanopowder (544876-5G), average particle size 50 nm or less, manufactured by Sigma-Aldrich
[0033] (Examples 1 to 3) Conductive particles and coated particles were placed in a screw-cap test tube containing zirconia balls (diameter 0.9 mm to 1.1 mm) as stirring members in the mixing ratio shown in Table 1, and the composite particles were prepared by stirring in a ball mill device, which was used as each Example. The amount of zirconia balls used and the stirring time are shown in Table 1. The stirring speed was 600 rpm. The screw-cap test tube used in the Examples and Comparative Examples had a diameter of 28 mm, a length of 105 mm, and a capacity of 30 mL.
[0034] Comparative Example 1 Only silver particles were used, and this was designated Comparative Example 1 consisting of only conductive particles. Comparative Example 2 Only gold particles were used, and this was designated Comparative Example 2 consisting of only conductive particles.
[0035] Scanning electron microscope photographs were taken of each of the Examples and Comparative Examples, and the particle aggregation and dispersibility were observed and evaluated as follows. SEM photographs are also shown for some of the Examples and Comparative Examples. ◎ The dispersibility was good, and almost no agglomerates with a long diameter more than 10 times the average particle size (value in the manufacturer's catalog) of the conductive particles used were observed. ○: Appropriate dispersion was observed, and agglomerates with long diameters more than 10 times the average particle size of the conductive particles used (manufacturer's catalog value) were observed, but agglomerates with long diameters more than 20 times larger were hardly observed. ×: There were many lumps due to aggregation, and a significant number of lumps with long diameters 20 times or more the average particle size (manufacturer's catalog value) of the conductive particles used were observed.
[0036] An SEM photograph of Example 1 is shown in Figure 2. In Figure 2, it was confirmed that the aggregated lumps observed in the case of single silver particles as seen in Figure 4 had broken down, and that the product was composed of multiple medium particles of about several µm to 10 µm. Although these medium particles appear to be clustered together in the SEM photograph, the macroscopic fluidity was good when used, and the medium particles were not in a state of strong aggregation with each other.
[0037] An SEM photograph of Example 3 is shown in Figure 3. In Figure 3, it was observed that the aggregated lumps observed in the case of single silver particles as seen in Figure 4 had broken down, forming independent medium-sized particles of about several µm to 10-odd µm.
[0038] 4 shows an SEM photograph of Comparative Example 1 before stirring. It was confirmed that the silver particles were aggregated and existed as clumps of several tens of μm in size.
[0039] For Comparative Example 1, 5.0 g of zirconia balls were placed in a screw-cap test tube, and 1.00 g of the silver particles of Comparative Example 1 was placed in the screw-cap test tube. The screw-cap test tube was then set in a ball mill and stirred at 600 rpm for 0.5 hours. FIG. 5 shows an SEM photograph of Comparative Example 1 after stirring. It was confirmed that the silver particles were deformed into flat particles of 10-odd μm to several tens of μm by stirring. When the coated particles were not used, it was presumed that the clumps of silver particles were not completely broken down by stirring, and were crushed by the zirconia balls due to their size.
[0040] Example 4 Next, a toner was prepared as follows, and this was designated as Example 4. Using the toner of Example 4, toner printing of an electric wiring circuit was performed. For the toner printing, the developing machine shown in FIG. 6 was used, and a photomask having the pattern shown in FIG. 7 was used. The photomask was modeled after a circuit around a microcomputer that is actually in circulation, and had a pattern with a 150 μm line / 350 μm space for the fine part. First, a target electrode for development was prepared as follows. A photoresist (OFPR-800; manufactured by Tokyo Ohka Kogyo Co., Ltd.) was dropped onto a glass substrate with ITO and applied in a thin film form using a spin coater, and then prebaked at 80°C for 10 minutes. The prebaked glass substrate and a photomask (see Figure 7) on which an IC circuit pattern was formed were set in an exposure device and exposed for 30 seconds. After exposure, the glass substrate was immersed in a developer for 90 seconds, then rinsed with pure water for 50 seconds, and postbaked at 100°C for 20 minutes. The postbaked glass substrate was immersed in an etching solution (ITO-06N; manufactured by Kanto Chemical Co., Ltd.) kept at 80°C in a hot water bath for 15 minutes. The glass substrate was then ultrasonically cleaned using acetone and isopropyl alcohol in that order for 10 minutes each. The glass substrate after cleaning was dried and spin-coated with an insulating film (TMR-P10; manufactured by Tokyo Ohka Kogyo Co., Ltd.), which was used as a target electrode for development.
[0041] 2.0 g of carrier particles (no coating agent, (not for sale); manufactured by Powder Tech Co., Ltd.) were placed in a screw-top test tube. Next, 0.04 g of nickel particles (Nickel nanopowder; average particle size 100 nm or less, manufactured by Sigma-Aldrich) were placed in the screw-top test tube, and the nickel particles were stirred by manual vibration. Then, 0.02 g of silver particles (Silver powder; average particle size 2 μm to 3.5 μm, manufactured by Sigma-Aldrich) were placed in the screw-top test tube, and the contents were stirred by manual vibration. Next, 0.02 g of the same silver particles were further placed in the screw-top test tube, and the contents were stirred again by manual vibration. Then, the screw-top test tube was set in a ball mill device, and stirred for 30 minutes at 600 rpm to prepare a toner (Example 4).
[0042] An acrylic plate 20 was set in the developing machine 10 shown in Fig. 6, and the toner (toner 40) prepared as described above was placed in it. The magnet 50 under the developing machine 10 was moved multiple times in the direction toward the front and rear of the page so that the toner 40 would be evenly distributed inside the developing machine. The surface of the target electrode was wiped with a Kimwipe thoroughly moistened with isopropyl alcohol, and the surface was allowed to air dry. After the magnet 50 was moved by the tire 60 so that the magnet 50 was not placed directly below the toner 40, the target electrode 30 was set in the developing machine 10, the power supply and earth were connected, the power supply was switched on, and the magnet 10 was moved back and forth continuously five times at a constant speed from directly below the toner 40 toward the front and rear of the paper surface under the conditions of an inter-plate distance of 1 mm and an applied voltage of 100 V, to perform development. When the developed product was observed as described above, it was visually confirmed that a highly precise wiring pattern was formed, as shown in Figure 7. Furthermore, when a line width of 150 μm of the developed product was observed with an optical microscope, it was confirmed that fine composite particles were well distributed within the line, and that the wiring was clearly drawn (developed).
[0043] It was confirmed that the toner of Example 4 described above can be used to perform high-definition toner printing that is compatible with printed electronics.
[0044] [Table 1] [Industrial Applicability]
[0045] The composite particles of the present invention are conductive and have excellent dispersibility, and therefore can be used in a variety of applications. For example, they can be suitably used as toner particles for toner printing in printed electronics. That is, the composite particles of the present invention are suppressed from self-aggregating and forming clumps, and therefore have good fluidity and are suitable as a conductive material contained in a toner. When the composite particles of the present invention are contained in a toner together with carrier particles, they are less likely to form clumps, and therefore are easily supported by the carrier particles, and can be successfully transferred to a target electrode in electrostatic printing and exhibit high resolution. Therefore, when a circuit electrode is patterned by toner printing using a toner containing the composite particles of the present invention, a high-definition pattern can be formed, and the high integration of semiconductor devices can be promoted.
[0046] The present invention described above encompasses the following technical ideas. (1) A conductive particle and a coated particle made of a material different from the conductive particle, A composite particle, characterized in that at least a portion of the surface of the conductive particle is covered with the covered particle. (2) The composite particle according to (1) above, wherein the coated particle contains a magnetic material. (3) The composite particle according to (1) or (2) above, wherein the conductive particle contains silver or gold. (4) The composite particles according to any one of (1) to (3) above, which are toner particles for forming metal wiring. (5) A toner comprising the composite particles according to any one of (1) to (4) above as toner particles. [Explanation of symbols]
[0047] 10. Developing machine 20...Acrylic plate 30...Target electrode 40. Toner 50 Magnet 60···Tire
Claims
1. A conductive particle made of only a substance exhibiting electrical conductivity, and a coated particle made of a material different from the conductive particle (excluding a thermoplastic resin), the coated particles include a conductive material, 2. A composite particle comprising a toner particle for forming a metal wiring, the toner particle comprising the conductive particle, at least a part of the surface of which is covered with the covering particle.
2. The composite particle according to claim 1 , wherein the coated particle comprises a magnetic material.
3. The composite particle according to claim 1 or 2, wherein the conductive particles comprise silver or gold.
4. The average particle size of the coated particles is 30 nm or more and 500 nm or less. A composite particle according to any one of claims 1 to 3.
5. A toner comprising the composite particle according to claim 1 as a toner particle.
Citation Information
Patent Citations
Production of magnetic toner
JP1992026862A
Conductive paste
JP1995307110A
Metal toner for formation of conductive pattern, carrier, and developer comprising the same
JP2003270846A
Electrically-charged powder, its manufacturing method, and defogging glass
JP2008218292A
Development method
JP2011257684A